Transformasi Digital Pemasaran Kaffahisme Ekonomi Islam: Transformasi Digital Pemasaran Dan Kaffahisme Ekonomi Islam - Ismail, Idhar (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2023)
Abstract: This study aims to determine the forms of digital marketing transformation and Islamic economic kaffahism and the implementation of digital marketing transformation towards Islamic economic kaffahism. the analytical method used in this research is descriptive analysis. Types of secondary data and data collection techniques used are literature studies or library research. Data analysis used is deductive, then conclusions are drawn from fact data or expert opinions on a particular problem. The results of the data findings are that there are three forms of digital marketing transformation in Islamic economic kaffahism, namely; Kafalah with collateral model; syamsirah with a profit-sharing model and mudharabah with a replica web model and the implementation of digital marketing transformation towards Islamic economic kaffahism can conclude that digital marketing transformation can be carried out if four conditions are met including: 1) endeavor; 2) benefits; 3) trust and 4) advice on digital marketing transformation values ​​(between business managers and business actors Market segmentation; Market positioning; Market entry strategy; Market mix strategy; and Timing strategy so that products are guaranteed, product benefits are guaranteed and product targets for people other. Keywords: Digital Marketing Transformation, Kaffahism, Islamic Economic Abstrak: Penelitian ini bertujuan untuk mengetahui bentuk-bentuk transformasi pemasaran digital dan kaffahisme ekonomi Islam serta implementasi transformasi pemasaran digital menuju kaffahisme ekonomi Islam. Metode analisis yang digunakan dalam penelitian ini adalah analisis deskriptif. Jenis data sekunder dan teknik pengumpulan data yang digunakan adalah studi literatur atau studi kepustakaan. Analisis data yang digunakan adalah deduktif, kemudian ditarik kesimpulan dari data fakta atau pendapat ahli terhadap suatu masalah tertentu. Hasil temuan data terdapat tiga bentuk transformasi digital marketing dalam kaffahisme ekonomi Islam, yaitu; Kafalah dengan model agunan; syamsirah dengan model bagi hasil dan mudharabah dengan model web replika serta penerapan transformasi digital marketing menuju kaffahisme ekonomi syariah dapat disimpulkan bahwa transformasi digital marketing dapat dilakukan jika terpenuhi empat syarat antara lain: 1) ikhtiar; 2) manfaat; 3) kepercayaan dan 4) saran nilai-nilai transformasi pemasaran digital (antara pengelola bisnis dan pelaku usaha Segmentasi pasar; Posisi pasar; Strategi masuk pasar; Strategi bauran pasar; dan Strategi pengaturan waktu agar produk terjamin, manfaat produk terjamin dan target produk untuk orang lain. Kata Kunci: Transformasi Pemasaran Digital, Kaffahisme, Ekonomi Islam